Vertical distribution of liverwort communities and their relationship with environmental factors in a karst sinkhole in south-western China. Issue 47 (25th December 2019) - Li, Chengyi; Zhang, Zhaohui; Li, Xiaofang; Wu, Jin; Wang, Zhihui
ABSTRACT: Understanding the relationships between the vertical distribution of liverwort communities and associated environmental factors is vital for biodiversity conservation in karst sinkholes. The abundance index, α and β diversity indices were used to analyse the characteristics of liverwort communities in the Monkey-Ear Sinkhole (280 m deep, entrance diameter 300 m, width 280 m). A Generalised Linear Model was used to study the vertical distribution of liverwort communities, and the relationships between their vertical distribution and environmental factors were analysed with Canonical Correspondence Analysis. Forty-two liverwort taxa from 22 genera in 19 families were identified in the sinkhole. The liverwort assemblages were dominated by the families Plagiochilaceae and Lejeuneaceae. The α and β diversity appeared to fluctuate randomly among the four depths sampled. The highest degree of environmental heterogeneity was found at the lower-middle section of the sinkhole; liverwort community diversity at the base was much higher than that found at the upper, middle or lower-middle sections. The environment at the base of the sinkhole was more complex than at the other three depths, providing a range of habitats that facilitated the coexistence of multiple liverwort communities. The abundance of species, genera and families in liverwort communities followed the sequence: base > upper section > middle section > lower – middle section. There were significant differences in liverwort communities at the four depths. In the sinkhole, liverwort communities fell into three distribution groups: wide, moderate or narrow distribution along the vertical direction. The communities with a broad distribution, found from the upper section to the base, were affected by a combination of light, humidity and temperature, and were classified as mixed factor dependent ; those with a moderate distribution found mostly in the mid and lower-middle sections were primarily dependent on temperature and humidity, and were classified as temperature and humidity dependent ; and those with a narrow distribution found at the base of the sinkhole were mainly influenced by humidity, and were classified as humidity dependent .